Islamic Branding Dalam Pandangan Tokoh Agama Kota Bangkalan - Kholid Romadhoni; Ach. Mus’if (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
This research is based on the economic context that occurs in the people of Bangkalan City in the development of Branding with Islamic terms. This study aims to analyze the opinions of religious leaders in the city of Bangkalan regarding Islamic branding, which still has a question mark regarding its urgency and existence among the people of the city of Bangkalan, especially. The researcher uses qualitative methods, namely research methods that focus on collecting data through observations of around Bangkalan City regarding several local brands that use Islamic Branding and on the other hand also focuses on conducting interviews and documentation to collect data about the views of Bangkalan religious leaders regarding Islamic Branding and Islamic Branding. existence in Bangkalan city to several religious figures in Bangkalan city. From the results of the study, the researcher stated and concluded that the views of religious leaders in Bangkalan city were divided into three groups. There are those who are aware of and acknowledge the existence of Islamic Branding in Bangkalan city, secondly there are those who are aware of but acknowledge the existence of Islamic Branding in Bangkalan city, third are not aware of and do not acknowledge the existence of Islamic Branding in Bangkalan city.